Sound imitative words in Beowulf - M. A. Flaksman (Дискурс, 2019)
Introduction. This article is devoted to the study of imitative (onomatopoeic and mimetic) lexicon of the Anglo-Saxon poem Beowulf. The poem is, probably, the most well-known work of Anglo-Saxon literature, characterized by its archaic language as well by its expressivity. The study focuses on quantitative and contextual analysis of the imitative words found in the poem from diachronic perspective.Materials and methods. Methods for the research include the method of continuous sampling, etymological analysis, historical-comparative analysis, elements of quantitative analysis, and the method of phonosemantic analysis. The study is conducted on the material of the full unabridged version of the Anglo-Saxon poem Beowulf written in Old English.Results. The results have revealed that all imitative words in the poem can be divided into three major semantic categories: 1) words denoting sounds of battle; 2) words denoting grief; 3) words denoting singing and playing musical instruments. There are altogether 43 imitative words identified in Beowulf, used 134 times. The calculations have shown that only 15 (or 35 %) out of them have been preserved since Old English.Discussion. We suggest the following reasons for the possible obsolesce of the Old English imitative words: 1) their replacement by the French loans, 2) their belonging to poetic language and subsequent fall out of use, 3) their replacement by other, newly-coined English imitative words. The last argument we deem as the most probable. The iconic treadmill hypothesis introduced earlier explains that the mass obsolesce of the Beowulf’s imitative words might have been caused by natural, evolutionary processes – regular sense and meaning development leading to the expressivity loss and overall de-iconization of the language’s imitative lexicon.Conclusions. The study of the poem demonstrated the diversity and dynamic nature of the English imitative lexicon as well as revealed the underlying tendency of imitative words’ de-iconization and replacement on the later stages of the language’s development.